Perspectives of people living with HIV on barriers to timely ART initiation following referral for antiretroviral therapy: A qualitative study at an urban HIV clinic in Kampala, Uganda. - Micheal Kiyingi; Joaniter I Nankabirwa; Christine Sekaggya Wiltshire; Joan Nangendo; John M Kiweewa; Anne R Katahoire; Fred C Semitala (Public Library of Science (PLoS), 2023)
Early initiation of antiretroviral therapy (ART) after HIV diagnosis prevents HIV transmission, progression of HIV to AIDS and improves quality of life. However, little is known about the barriers to timely ART initiation among patients who test HIV positive in settings different from where they will receive HIV treatment, hence are referred in the routine setting. Therefore, we explored the perspectives of people living with HIV on barriers faced to initiate ART following HIV testing and referral for treatment. In this qualitative study, we purposively sampled and enrolled 17 patients attending the Mulago ISS clinic. We selected patients (≥18 years) who previously were received as referrals for HIV treatment and had delayed ART initiation, as ascertained from their records. We conducted in-depth interviews, which were audio recorded, transcribed and translated. We used Atlas.ti version 9 software for data management. Data analysis followed thematic and framework analysis techniques and we adopted the socio-ecological model to categorize final themes. Key themes were found at organizational level including; negative experiences at the place of HIV diagnosis attributed to inadequate counselling and support, unclear communication of HIV-positive results and ambiguous referral procedures; and, long waiting time when patients reached the HIV clinic. At individual level, the themes identified were; immediate denial with late acceptance of HIV-positive results attributed to severe emotional and psychological distress at receiving results, fear of perceived side effects and long duration on ART. At interpersonal level, we found that anticipated and enacted stigma after HIV diagnosis resulted in non-disclosure, discrimination and lack of social support. We found that challenges at entry (during HIV test) and navigation of the HIV care system in addition to individual and interpersonal factors contributed to delayed ART initiation. Interventions during HIV testing would facilitate early ART initiation among patients referred for HIV care.